Web Site Story: A Teacher Web Site and Its Usefulness to Parents and Students - Harkness, Deana (My University, 2006)
This study involves action research concerning a teacher Web site and its usefulness to both parents and students. The research site is a grade 7-8 public school in a rural county of northeast Georgia. Participants received Web site training and used the Web site for a three-week period. The researcher used a hit counter to monitor page use, observed students using the site in weekly computer lab visits, and compiled survey and interview responses from parents and students. The findings report that the Web site was beneficial for students and their parents and that the classroom presentations, quizzes and useful links pages were used most often.
Keywords: Teacher Web site; Hit counter; Page use